Dampak Kesehatan Mental dan Atmosfer kerja Terhadap Motivasi Kerja Karyawan: Studi Kasus pada Karyawan Swasta di Kota Surabaya - Isnawati Isnawati; Nur Farida; Nur Aini Anisa (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
Isnawati The Impact of Mental Health and Work Atmosphere on Employee Work Motivation (Case Study on Private Employees in Surabaya City), Institut of Economic Science Pemuda Surabaya, Mentor Nur Farida, S.M., M.M. The purpose of this research is to determine how the working environment and mental health of private employees in the Surabaya City area affect their motivation for their jobs. 150 private workers from a range of industrial sectors made up the research sample. A Likert scale questionnaire survey is employed as the data collection method to gauge factors related to job motivation, workplace culture, and mental wellness. The findings of data analysis using SPSS indicate that private employees' motivation at work is significantly positively impacted by their mental health and the environment in which they operate. The results of the partial t-test indicate that job motivation is significantly impacted to some extent by mental health and the work environment. Simultaneous F tests verify that work motivation is significantly impacted by both mental health and the workplace environment.